Berger Code Based Concurrent Online Self-Testing of Embedded Processors - G. Prasad Acharya; M. Asha Rani (Institute of Advanced Engineering and Science, 2018)
In this paper, we propose an approach to detect the temporary faults induced by an environmental phenomenon called single event upset (SEU). Berger code based self-checking checkers provides an online detection of faults in digital circuits as well as in memory arrays. In this work, a concurrent Berger code based online self- testable methodology is proposed and integrated in 32-bit DLX Reduced Instruction Set Computer (RISC) processor on a single silicon chip. The proposed methodology is implemented and verified for various arithmetic and logical operations of the DLX processor. The FPGA implementation of the proposed design shows that a meager increase in hardware utilization facilitates online self- testing to detect temporary faults.